Assessing Models of Public-Private Partnership for Irrigation Development in Tanzania - Meinzen-Dick, Ruth S. (2016)
Presented by IFPRI Senior Research Fellow Ruth Meinzen-Dick and University of Dar Es Salaam Professor Faustin Maganga at Workshop on “New Directions for Irrigation in Tanzania: The Context of Public Private Partnership” on September 2, 2016. https://www.ifpri.org/event/new-directions-irrigation-development-tanzania